Therapeutic Potential of Kaempferia galanga L. Extract in Ameliorating Oxidative Stress and Metabolic Dysregulation in a Rat Model of Metabolic Syndrome - Hasimun, Patonah; Muzaki, Yoga Adi Restu; Sukmawati, Ika Kurnia; Zahra, Nadhira Aulia; Kusriani, Herni (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Metabolic syndrome is associated with an increased risk of hypertension, diabetes, and cardiovascular disease, which are often triggered by oxidative stress and inflammation. This study evaluated the effects of Kaempferia galanga L extract (ERK) on oxidative stress and metabolic dysfunction using a fructose-induced male Wistar rat model. A total of 25 rats were divided into five groups: normal control, positive control, allopurinol group, and two ERK treatment groups at doses of 50 and 100 mg/kg body weight. All groups, except the normal control, were given 25% fructose in the drinking water and an injection of potassium oxonate (4.5 mg/kg body weight) for 28 days. Evaluation was done by measurement of glucose, triglyceride, malondialdehyde (MDA) and nitric oxide (NO) and histological analysis of aortic tissue. The results showed that ERK, especially at a dose of 100 mg/kg, significantly reduced glucose, triglyceride and MDA levels and increased NO levels. ERK administration also reduced the body weight of mice and prevented the formation of foam and inflammatory cells in aortic tissue. The total flavonoid content of ERK also supports its biological activity. This study concludes that ERK has potential as a natural therapeutic agent to treat metabolic syndrome through antioxidant and anti-inflammatory mechanisms.